Hidrogênio verde no Brasil: desafios e oportunidades - Campos, Maria Julia Almeida Carneiro de (Universidade Federal de São Carlos, 2025)
Green hydrogen has gained prominence as a promising renewable energy alternative, recognized for its ability to generate energy without carbon emissions. This sector is rapidly growing and attracting significant investments, with the potential to play a crucial role in the global energy transition. In this context, the present work aims to analyze the current state of green hydrogen, its advantages, disadvantages, challenges, and opportunities. To achieve this general objective, the methodology used was based on a bibliographic review. Among the results, it was identified that green hydrogen reduces greenhouse gas emissions and helps further diversify a country's energy matrix. However, despite its advantages, green hydrogen still faces significant challenges. The high production costs, the need for adequate infrastructure for transportation and storage, and issues related to technological efficiency are barriers that need to be overcome. Both internationally and in the national context, expectations are optimistic for reducing production costs, driven by technological advances and large-scale projects aimed at optimizing storage and transportation infrastructure. In Brazil, the country stands out as a strong candidate to become a global leader in green hydrogen production, thanks to the wide availability of renewable sources such as solar and wind energy. Furthermore, Brazil has a vast domestic market and is investing in international partnerships to strengthen the green hydrogen industry.
Green hydrogen in Brazil: challenges and opportunities
Keywords: Matriz energética; Energia renovável; Sustentabilidade; Energy matrix; Renewable energy; Sustainability; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; 7. Energia limpa e acessível; 11. Cidades e Comunidades Sustentáveis; 13. Ação contra a Mudança Global do Clima